Причини впливу кризових ситуацій на діяльність підприємств - Карковська, В. Я.; Хомин, Р. М.; Якимець, М. М.; Судомир, Н. Ю.; Karkovska, V. Y.; Khomyn, R. M.; Yakymets, M. M.; Sudomyr, N. U. (Видавництво Львівської політехніки, 2019)
У статті розглянуто підсистеми виробничої та управлінської діяльності підприємства, виокремлено основні напрями його діяльності. Проаналізовано прикладні ситуації впливу кризових явищ на збутове, матеріально-технічне, кадрове, інформаційне, управлінське, інноваційне, ресурсне та фінансове забезпечення. Встановлено основні причини впливу кризових явищ на діяльність підприємства. Наведено найтиповіші наслідки негативного впливу кризових ситуацій в розрізі напрямів роботи підприємства.

The current macroeconomic situation shows that it is difficult for domestic enterprises to withstand the effects of threats. Therefore, research in this direction remains relevant in the future. The development of methodological recommendations for solving the problems of financial and economic security of enterprises and organizations is aimed, first of all, in determining the most vulnerable directions of activity of enterprises and to choose the optimal tools for activating their work. The article deals with subsystems of production and management of the enterprise, outlines the main directions of its activity. One of the external threats to the financial and economic security of enterprises is the crisis. In particular, in the context of the economic crisis, the priority direction of the business entities is to coordinate actions to reduce the impact of crisis phenomena on the financial sector. It is obvious that ignoring the state of financial and economic security can lead to catastrophic consequences: decline, bankruptcy, and further liquidation of the enterprise. The applied situations of the impact of crisis phenomena on the sales, logistical, human resources, information, management, innovation, resource and financial support are analyzed, as this is directly connected with the provision of the appropriate level of financial and economic security. The basic causes of the influence of crisis phenomena on the activity of the enterprise are established. The most typical consequences of the negative influence of crisis situations in the context of the work of the enterprise are given, namely: the loss of the possibility of acquiring the necessary nomenclature of material and technical resources due to insolvency of dealerssuppliers, belonging to a group of economic entities most vulnerable to the impact of the crisis; increase in the cost of material resources, which negatively affects price competition; a sharp decline in labor productivity and fluidity of skilled personnel; destruction of economic ties with contractors; lack of appropriate level of skills of workers and specialists, moral and physical deterioration of production assets, which will lead to increased costs for product quality control and the growth of defective products; increase in production costs; reduction in the number of orders and sales contracts; increase in the cost of production and a sharp decline in labor productivity; an increase in the amount of illiquid working capital and, as a result, the presence of excess stockpiles; a significant decrease in sales volumes and, as a result, a lack of revenue from sales of products, etc.
The influence of crisis situations on the activities of enterprises
Keywords: підрозділи підприємств; причини впливу кризових явищ; наслідки кризи; зовнішні загрози; фінансово-економічна безпека; організаційна системи; divisions of enterprises; causes of the impact of crisis phenomena; consequences of crisis; problems; external threats; financial and economic security; organizational systems; 65.050.012.32